2012
DOI: 10.1002/pi.4266
|View full text |Cite
|
Sign up to set email alerts
|

Flow behavior of hydroxypropyl methyl cellulose/polyacrylic acid interpolymer complexes in aqueous media

Abstract: The intermolecular complexation of non‐ionic polymers with weak acids having chemically complementary structures is an important approach to modify the viscosity of polymer solutions. In this study intermolecular complexation of hydroxypropyl methyl cellulose (HPMC) with polyacrylic acid (PAA) in an aqueous medium was studied. The study focuses on the factors affecting the complexation and rheological behavior of the HPMC/PAA system including the stoichiometric ratio of the two polymers, the molecular weight o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Complexation between cellulose derivatives, such as HPMC, and poly(acrylic acid) (PAA) has been reported previously. [14][15][16][17] It was found that the polymers form IPC in acidic medium (such as pH 3.0) and it was confirmed that hydrogen bonding was a major driving force of this interaction. [14] At higher pH values (pH 9), due to ionization of the PAA, interpolymer associates may form accompanied with an increase in viscosity of the solution mixture.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Complexation between cellulose derivatives, such as HPMC, and poly(acrylic acid) (PAA) has been reported previously. [14][15][16][17] It was found that the polymers form IPC in acidic medium (such as pH 3.0) and it was confirmed that hydrogen bonding was a major driving force of this interaction. [14] At higher pH values (pH 9), due to ionization of the PAA, interpolymer associates may form accompanied with an increase in viscosity of the solution mixture.…”
Section: Introductionmentioning
confidence: 86%
“…A detailed discussion on the formation HPMC/PAA IPCs and associates as a function of pH and ionic strength of the medium can be found in our previous paper. [17] 3.2.2. HPMC/PEI polymer mixtures.…”
Section: Hpmc/paa Ipcs and Associatesmentioning
confidence: 98%
See 3 more Smart Citations